Evaluacion de la irradiación térmica en incendio por bleve en el área de tanques de almacenamiento de crudo y su incidencia en afectación por quemaduras de los trabajadores de la C.I.A. OIl Ecuador en la región Amazónica. Propuesta implementar un plan de emergencia. - Cando Portilla, Luis Eduardo (2016)
Project prior to obtaining the academic degree as a Magister in Production Management under the title: ¨Evaluation of Thermal Radiation by Bleve fire in the storage tanks area of raw oil and its incidence and impact in the burns of workers of the C.I.A. OIL Ecuador in the Amazon Region¨. The main objective of this research ranges from identifying the effective time of exposure to thermal radiation on fire by Bleve to the atmospheric, geometric and physical – chemical properties evaluation; involving heat irradiation conditions in order to set up control measures against critical points, measured in this evaluation. The hypothesis is to verify whether the thermal irradiation by Bleve fire burns affects to the workers in the raw oil tanks storage area of the company. To sustain this statement, the following results were found by using appropriate research methods for the viability of their results, identifying the exposure effective time to thermal radiation on Bleve fire in around 4 minutes; time that takes workers to reach to the meeting point. The weather condition of the site under study is around 80% of relative humidity at a temperature of 24o C. While the geometric conditions (average values) of thermal irradiation in Belve fire of the three raw oil storage tanks are: diameter of the fireball 731.77 meters, flame height 548.33 meters and 203.12 meters of distance between the fireball to the irradiation point. The physical – chemical properties are based on the type of raw oil to be stored in those tanks. The burns affecting the workers were obtained using the probit method, where the intensity of the Bleve thermal irradiation was 98.39 kW / m2, giving a very high Probit result, meaning that 100% of the workers suffer burns and death too.